2016
DOI: 10.5194/tc-2016-79
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fram Strait sea ice export variability and September Arctic sea ice extent over the last 80 years

Abstract: Abstract. The Arctic Basin exports between 600,000 and 1 million km2 of it's sea ice cover southwards through Fram Strait each year, or about 10 % of the sea-ice covered area inside the basin. During winter, ice export results in growth of new and relatively thin ice inside the basin, while during summer or spring, export contributes directly to open water further north that enhances the ice-albedo feedback during summer. A new updated time series from 1935 to 2014 of Fram Strait sea ice area export shows that… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(74 citation statements)
references
References 0 publications
3
69
2
Order By: Relevance
“…Variations in sea level pressure gradient explained approximately 60% of the variability in sea ice motion in Fram Strait (Widell et al, ), indicating the important role of atmospheric forcing on sea ice motion and distribution in Fram Strait, superimposed on a general southward drift out of the Arctic Ocean in western Fram Strait. Smedsrud et al () reported weakest export of sea ice and lowest sea ice drift speeds in Fram Strait in summer (July and August), which suggests that sea ice motion is likely even more susceptible to governing wind patterns in Fram Strait at this time of year. As seen from monthly mean winds (Figure ), wind forcing was very different in the 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in sea level pressure gradient explained approximately 60% of the variability in sea ice motion in Fram Strait (Widell et al, ), indicating the important role of atmospheric forcing on sea ice motion and distribution in Fram Strait, superimposed on a general southward drift out of the Arctic Ocean in western Fram Strait. Smedsrud et al () reported weakest export of sea ice and lowest sea ice drift speeds in Fram Strait in summer (July and August), which suggests that sea ice motion is likely even more susceptible to governing wind patterns in Fram Strait at this time of year. As seen from monthly mean winds (Figure ), wind forcing was very different in the 2 years.…”
Section: Discussionmentioning
confidence: 99%
“…Sea ice drift through Fram Strait is primarily wind driven (Kwok et al, ; Smedsrud et al, ). Trends in both Fram Strait outflow and near‐surface wind over Fram Strait have been positive since 1957 (Smedsrud et al, ). However, since 1979 there has been no significant positive trend in Arctic‐average near‐surface wind speed, and so the positive trend in Arctic‐average sea ice drift speed during this time is likely due to sea ice thinning (Rampal et al, ; Spreen et al, ).…”
Section: Drivers Of Long‐term Trends During Wintermentioning
confidence: 99%
“…Atmospheric winds are a key driver of sea ice motion, and numerous studies have suggested that changes in the atmospheric circulation act to accelerate the rate of sea ice loss. In particular, it has been proposed that changes in the atmospheric circulation lead to increased export of sea ice through Fram Strait (Langehaug et al, ; Rampal et al, ; Smedsrud et al, ; Wettstein & Deser, ; Williams et al, ). These changes in the atmospheric circulation are in turn connected to large‐scale changes in sea level pressure (Deser et al, ; Kwok et al, ; Rigor et al, ; Screen et al, ; Serreze et al, ; Wettstein & Deser, ).…”
Section: Introductionmentioning
confidence: 99%
“…Figure 1a). The smaller Atlantic-side trend is due in part to the ubiquity of Fram Strait export maintaining some measure of ice cover in that sector [e.g., Smedsrud et al, 2016], although as Table 1 demonstrates, the trends in variability are small in all but the Kara Sea on the Atlantic side. Indeed, the variability in open water fraction in the Pacific sector is more than an order of magnitude greater than in than the Atlantic sector.…”
Section: Regional Circulationmentioning
confidence: 99%